Problems of The Flexible Planning and Design Interaction Between The Components of ‎Hospitals For Endemic and Epidemic Diseases, Internally and Externally.‎ (Journal of University of Babylon for Engineering Sciences, 2024)
Hospital design has a major impact on the environment and on the health and well-being of patients. Hospitals for endemic diseases have a great impact and connection with the environment. Therefore, principles and foundations must be followed that enhance environmental protection and provide a good internal environment in this type of hospital, because here epidemics that are transmitted in different ways are dealt with. Therefore, there are principles followed in the design of these hospitals that take into account the locations of the internal departments. The hospital and its functional relationships with each other and their locations relative to the external environment and how to achieve environmental comfort in the hospital and achieve protection from the external environment and protect the external environment from the transmission of epidemics from the hospital to the outside. This depends on the way in which the spaces of the hospital’s epidemiological departments are designed and the extent of the application of planning principles and controls. Designed to achieve the required protection internally and externally.